Oncoplastic surgery (Plastic and Reconstructive Surgery,, 2018)
This book introduces oncoplastic surgery as an interdisciplinary branch of oncological surgery that integrates theories and technologies in oncological surgery, plastic surgery and microsurgery with characteristics of planned radical resection of tumors and one-stage repair and reconstruction of surgical defects on the basis of multidisciplinary treatment (MDT) of tumors. Consisting of 23 chapters, the book covers a range of surgical topics related to oncoplastic surgery in clinical disciplines, with a focus on oncology surgery, plastic surgery, microsurgery, vascular surgery, otolaryngology-head and neck surgery, neurosurgery, oral and maxillofacial surgery, breast surgery, urinary surgery, gynecologic oncology, bone surgery, thoracic surgery and abdominal surgery. In most of the surgical cases oncology surgery is combined with plastic surgery. The book summarizes the basic theories and clinical experiences in oncoplastic surgery, focusing on repair and aesthetic reconstruction after tumor removal, which increases patients' survival rate and significantly improves their quality of life. It is a valuable reference resource for tumor surgeons, plastic surgeons, head and neck surgeons, breast surgeons as well as surgeons in other relevant fields. Editor Xiao Zhou is a Professor at the Department of Oncology Plastic Surgery, Hunan Cancer Hospital, The Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University, Changsha , China. Editor Yilin Cao and Wei Wang are Professors and Plastic and Reconstructive surgeons of Shanghai Ninth People's Hospital, China.